REORIENTASI KEBIJAKAN MONETER INFLATION TARGETING - Wolok, Tineke (Jurnal Pelangi Ilmu, 2009)
The high inflation suggests the economic crisis in Indonesia recently. The government implements the inflation targeting in monetary policy to recovery the economic stability. Nevertheless, this policy can perform merely the precondition of inflation targeting had been fulfilled. And apparently, this policy can be difficult to realize, because the precondition was complicated and exactly became the obstacle.